IMPLEMENTASI PLASMA DINGIN SEBAGAI MEDIA STERILISASI MENGGUNAKAN METODE DIELECTRIC BARRIER DISCHARGE - Muhamad Ibnu Fajar; Eka Maulana; n/a Rahmadwati (Jurnal Mahasiswa TEUB, 2021)
ABSTRAKPlasma ialah wujud zat keempat yang merupakan gas terionisasi. Berdasarkan temperaturnya, plasma dapat dikategorikan menjadi plasma bertemperatur tinggi (thermal/equilibrium plasma) dan plasma bertemperatur rendah (cold plasma/non-equilibrium). Plasma dingin adalah plasma yang memiliki suhu ruang dan terjadi dalam keadaan ketidaksetimbangan termal (non–thermal equilibrium) antara temperatur elektron dan gas. Plasma dapat terbentuk secara alami seperti mataharidan dapat dibuat melalui pemberian energi pada gas sehingga terjadi ionisasi. Metode pembangkit plasma dingin melaluidielectric barrier discharge bertujuan untuk arus listrik yang dialirkan melalui elektroda agar tidak sampai terjadi arc ataubunga api yang bisa membuat short suatu rangkaian elektronik. Penggunaan lapisan dielectric bertujuan untuk menghindari kondisi tersebut sehingga arus listrik bisa berubah menjadi plasma dalam kondisi corona discharge. Peristiwa loncatanlistrik pada fluida seperti udara, namun dalam kondisi belum mencukupi untuk terjadi arc atau electrical breakdowndisebut corona discharge. Plasma memiliki sifat reaktif sehingga dapat dimanfaatkan untuk inaktivasi mikroorganisme. Proses tersebut dapat diimplementasikan dengan cara pembuatan rangkaian elektronik yang mampu membangkitkantegangan tinggi melalui flyback transformer. Rangkaian driver flyback transformer mengubah tegangan 24 V DC menjadi15-20 kV 15-40 kHz. Keluaran rangkaian dihubungkan dengan elektroda berlapis dielectric agar terbentuk plasma dingin. Plasma dingin dipaparkan pada objek yang akan disterilisasi selama 5 detik hingga 60 detik. Pengujian efektivitas sterilisasiplasma dingin melalui uji lab mikrobiologi untuk mengetahui mikroorganisme dapat tumbuh atau inaktivasi. Prosesinaktivasi mikroorganisme terjadi karena plasma bersifat reaktif terhadap dinding sel mikroorganisme.ABSTRACTPlasma is the fourth state of matter which is an ionized gas. Based on the temperature, plasma can be categorized into hightemperature plasma (thermal/equilibrium plasma) and low temperature plasma (cold plasma/non-equilibrium). Coldplasma is plasma that has room temperature and occurs in a state of thermal equilibrium (non-thermal equilibrium)between the electron and gas temperatures. Plasma can form naturally like the sun and can be made by energizing the gasso that ionization occurs. The method of generating cold plasma through a dielectric barrier discharge aims for an electriccurrent to flow through the electrodes so that there is no arc or spark that can short an electronic circuit. The use of adielectric layer aims to avoid this condition so that the electric current can turn into plasma in a corona dischargecondition. The event of an electric jump in a fluid such as air, but in insufficient conditions for an arc or electrical breakdown to occur is called a corona discharge. Plasma has reactive properties so that it can be used for inactivation ofmicroorganisms. This process can be implemented by making electronic circuits capable of generating high voltagesthrough flyback transformers. Driver flyback transformer circuit convert input voltage 24 V DC into 15-20 kV 15-40kHz.The output of the circuit is connected to a dielectric-coated electrode to form a cold plasma. Cold plasma is exposed to theobject to be sterilized for 5 seconds to 60 seconds. Testing the effectiveness of cold plasma sterilization throughmicrobiology lab tests to determine whether microorganisms can grow or inactivate. The process of inactivation ofmicroorganisms occurs because plasma is reactive to the cell walls of microorganisms. The habit of Indonesian people inwashing their hands (hand hygiene) is classified as low, it is recorded that an average of 12% of people wash their handswith soap. Washing hands can reduce the transmission of microorganisms between those in the environment and the body.How to wash your hands can be done through hand washing and hand rub. The impact of excessive use of soap, antisepticand disinfectants can affect the environment and skin health, for example skin irritation, respiration, and eyes. In order tobe hygienic, sterilization can be done both on the body, items and the room. One method that can be applied is to use coldplasma. Cold plasma is an ionized gas that occurs in a state of thermal imbalance. The cold plasma generation methodused is dielectric barrier discharge so that the discharge at the electrodes can be dislodged by the dielectric layer andplasma arises. The implementation of the system design consists of a flyback transformer driver circuit that changes the 24V DC voltage to 15-20 kV 15-40 kHz. The electrode design is made of acrylic which is connected to the secondary leg ofthe flyback transformer. Cold plasma has an effective ability to decontaminate microorganisms because it has ionizedparticles and reactive molecules. The system design is implemented successfully for the sterilization of microorganisms.Sterilization media made of acrylic can produce plasma. The mechanism of sterilization in microorganisms occurs due toplasma ionization reactions which oxidize the cell walls of microorganisms, thereby inhibiting growth and causinginactivation of microorganisms.